Dysregulated expression of death, stress and mitochondrion related genes in the sciatic nerve of presymptomatic SOD1G93A mouse model of Amyotrophic Lateral Sclerosis - Alves, Chrystian J.; Maximino, Jessica R.; Chadi, Gerson (Frontiers in Cellular Neuroscience, 2015)
Schwann cells are the main source of paracrine support to motor neurons. Oxidative stress and mitochondrial dysfunction have been correlated to motor neuron death in Amyotrophic Lateral Sclerosis (ALS). Despite the involvement of Schwann cells in early neuromuscular disruption in ALS, detailed molecular events of a dying-back triggering are unknown. Sciatic nerves of presymptomatic (60-day-old) SOD1G93A mice were submitted to a high-density oligonucleotide microarray analysis. DAVID demonstrated the deregulated genes related to death, stress and mitochondrion, which allowed the identification of Cell cycle, ErbB signaling, Tryptophan metabolism and Rig-I-like receptor signaling as the most representative KEGG pathways. The protein-protein interaction networks based upon deregulated genes have identified the top hubs (TRAF2, H2AFX, E2F1, FOXO3, MSH2, NGFR, TGFBR1) and bottlenecks (TRAF2, E2F1, CDKN1B, TWIST1, FOXO3). Schwann cells were enriched from the sciatic nerve of presymptomatic mice using flow cytometry cell sorting. qPCR showed the up regulated (Ngfr, Cdnkn1b, E2f1, Traf2 and Erbb3, H2afx, Cdkn1a, Hspa1, Prdx, Mapk10) and down-regulated (Foxo3, Mtor) genes in the enriched Schwann cells. In conclusion, molecular analyses in the presymptomatic sciatic nerve demonstrated the involvement of death, oxidative stress, and mitochondrial pathways in the Schwann cell non-autonomous mechanisms in the early stages of ALS.